Can YouTube-based instructional videos improve statistical reasoning skills? - Aeng Muhidin; Shinta Doriza (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study investigates the potential of YouTube-based instructional videos to improve students’ statistical reasoning skills in the context of learning Educational Statistics. Statistical reasoning is a fundamental competency in this subject; however, many students face difficulties in grasping and applying statistical concepts due to instruction that is often abstract and overly theoretical. To address this issue, the study was conducted to assess whether integrating YouTube as a learning medium could provide more concrete and accessible explanations, thereby enhancing students’ understanding. The study employed a quasi-experimental one-group pretest-posttest design. Data were collected from undergraduate students enrolled in an Educational Statistics course using two instruments: a procedural knowledge test and a perception questionnaire. The results revealed a statistically significant improvement in students’ statistical reasoning skills after participating in the YouTube-based learning intervention. Additionally, students expressed positive perceptions toward the use of YouTube videos in learning statistics. The highest average ratings were reported in learning effectiveness (M = 98), followed by learning motivation (M = 96), content clarity (M = 92), and ease of access (M = 87). These findings suggest that YouTube can serve as an effective digital learning tool to support conceptual understanding in technical subjects, highlighting the importance of integrating digital media in higher education pedagogy. Abstrak Penelitian ini mengkaji potensi penggunaan video pembelajaran berbasis YouTube dalam meningkatkan keterampilan penalaran statistik mahasiswa pada mata kuliah Statistika Pendidikan. Penalaran statistik merupakan kompetensi mendasar yang menuntut mahasiswa memahami dan menginterpretasikan data. Namun, banyak mahasiswa mengalami kesulitan akibat penyampaian materi yang cenderung abstrak dan teoretis. Oleh karena itu, dibutuhkan inovasi pembelajaran yang lebih konkret dan mudah diakses. Penelitian ini menggunakan desain kuasi-eksperimen dengan pendekatan one-group pretest-posttest. Partisipan terdiri dari mahasiswa program sarjana yang mengikuti mata kuliah Statistika Pendidikan. Data dikumpulkan melalui dua instrumen, yaitu tes pengetahuan prosedural dan kuesioner persepsi mahasiswa terhadap media pembelajaran. Hasil penelitian menunjukkan peningkatan yang signifikan secara statistik dalam keterampilan penalaran statistik setelah pembelajaran berbasis YouTube. Selain itu, respons mahasiswa terhadap penggunaan YouTube sangat positif. Nilai rata-rata tertinggi diperoleh pada kategori efektivitas pembelajaran (M = 98), diikuti motivasi belajar (M = 96), kejelasan konten (M = 92), dan kemudahan akses (M = 87). Temuan ini mengindikasikan bahwa YouTube merupakan media pembelajaran digital yang efektif dalam mendukung pemahaman konseptual mahasiswa, terutama pada mata kuliah yang bersifat teknis. Oleh karena itu, integrasi media digital seperti YouTube perlu dipertimbangkan secara serius dalam pengembangan pedagogi pendidikan tinggi. Kata Kunci: kepuasan belajar; penalaran statistik; video pembelajaran; statistika pendidikan